Sediaan krim ekstrak jeruk nipis (Citrus aurantifolia S.) Sebagai Obat luka sayat pada mencit jantan (Mus musculus) - Madani Sirait; Gabena Indrayani Dalimunthe; Minda Sari Lubis; D. Elysa Putri Mambang (Journal of Pharmaceutical and Sciences, 2023)
Indonesia is a country that is rich in plant diversity. One of them is lime, which is used as a traditional wound medicine. Lime contains essential oil compounds, flavonoids, saponins, tannins, alkaloids, citric acid, amino acids, vitamin B1, and vitamin C. Based on previous research, flavonoids, tannins, and saponins can heal wounds. Making simplicia using an oven at 50oC  and characterizing simplicia Extraction using the maceration method with 96% ethanol is then concentrated using a rotary evaporator. Orientation on the preparation of the cream was carried out until a good cream texture was found, and a cream preparation test was carried out to comply with the requirements in the literature. The test animals used were 24 male mice, which were divided into six treatment groups. The first group was treated with betadine, the second group was treated with cream without extract, the third group was treated with 2 grams of extract cream, the fourth group was treated with 3 grams of extract cream, the fifth group was treated with 4 grams of extract cream, and the sixth group was untreated. Each group was given a 10-mm wound. Based on the treatment carried out for 14 days, the best formulation was a 4-gram lime extract cream, and the wound healed on day 9, which was the same as the comparison used, namely betadine.